VITAMIN D INSUFFICIENCY: WHAT'S NEW? - I. N. Zakharova; Yu. A. Dmitrieva; S. V. Yablochkova; E. A. Evseeva ("Paediatrician" Publishers LLC, 2014)
Currently, scientists are continuing discussions on the definition of the precise level of vitamin D in the blood serum, but there is a consensus that vitamin D insufficiency is common throughout the world and has an adverse effect on human health. To make vitamin D provided all the necessary positive effects on the human body should maintain its status in the body at the proper level. That is why it is important to evaluate the content of vitamin D in the blood for the detection of insufficiency and deficiency.